Diagnostic Contribution of Donor-Specific Antibody Characteristics to Uncover Late Silent Antibody-Mediated Rejection—Results of a Cross-Sectional Screening Study. Issue 3 (March 2017) - Eskandary, Farsad; Bond, Gregor; Kozakowski, Nicolas; Regele, Heinz; Marinova, Lena; Wahrmann, Markus; Kikić, Željko; Haslacher, Helmuth; Rasoul-Rockenschaub, Susanne; Kaltenecker, Christopher C.; König, Franz; Hidalgo, Luis G.; et al.
Abstract : Background: Circulating donor-specific antibodies (DSA) detected on bead arrays may not inevitably indicate ongoing antibody-mediated rejection (AMR). Here, we investigated whether detection of complement-fixation, in parallel to IgG mean fluorescence intensity (MFI), allows for improved prediction of AMR. Methods: Our study included 86 DSA+ kidney transplant recipients subjected to protocol biopsy, who were identified upon cross-sectional antibody screening of 741 recipients with stable graft function at 6 months or longer after transplantation. IgG MFI was analyzed after elimination of prozone effect, and complement-fixation was determined using C1q, C4d, or C3d assays. Results: Among DSA+ study patients, 44 recipients (51%) had AMR, 24 of them showing C4d-positive rejection. Although DSA number or HLA class specificity were not different, patients with AMR or C4d + AMR showed significantly higher IgG, C1q, and C3d DSA MFI than nonrejecting or C4d-negative patients, respectively. Overall, the predictive value of DSA characteristics was moderate, whereby the highest accuracy was computed for peak IgG MFI (AMR, 0.73; C4d + AMR, 0.71). Combined analysis of antibody characteristics in multivariate models did not improve AMR prediction. Conclusions: We estimate a 50% prevalence of silent AMR in DSA+ long-term recipients and conclude that assessment of IgG MFI may add predictive accuracy, without an independent diagnostic advantage of detecting complement-fixation. Abstract : The authors report their experience on 86 DSA+ kidney transplant recipients with available screening biopsies. They confirm that about 50% of these patients do experience subclinical ABMR and compare the prognostic information given by IgG MFI level, C1q- and C3d-fixing properties of DSAs.